201k views
0 votes
HELP PLZ AND THANKS

HELP PLZ AND THANKS-example-1
User Kimamula
by
6.8k points

2 Answers

5 votes

The first equation y = 3x-10 basically says that y is the same as 3x-10. This will allow us to make a replacement in the second equation. This is what the substitution rule allows us to do.

2x + 3y = 3

2x + 3( y ) = 3

2x + 3( 3x-10) = 3 ... replace y with 3x-10

2x+3(3x) + 3(-10) = 3 ... distribute

2x + 9x - 30 = 3

11x - 30 = 3

11x-30+30 = 3+30 ... add 30 to both sides

11x = 33

11x/11 = 33/11 ... divide both sides by 11

x = 3

Now that we know x = 3, we use it to find the value of y. You can use any equation with x and y in it. The easiest is where y is already isolated

y = 3x - 10

y = 3*3 - 10 ... replace x with 3

y = 9 - 10

y = -1

Final Answer: choice D; the ordered pair (3,-1)

User Rodgobbi
by
6.2k points
3 votes

Answer:

(3,-1)

Hope this helped u ^_^


User WernerW
by
5.6k points